Assessment of Soy-Based Imports into the US and Associated Foreign Animal Disease Status - Allison K. Blomme; Cassandra K. Jones; Jordan T. Gebhardt; Jason C. Woodworth; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
Soy-based products are known to pose a viable risk to US swine herds because of their ability to harbor and transmit virus. This study evaluated soy imports into the US as a whole and from foreign animal disease positive (FAD+) countries to determine which products are being imported in the highest quantities and observe potential trends in imports from FAD+ countries. Import data were accessed through the United States International Trade Commission website (USITC DataWeb) and summarized using R (version 4.0.2, R core team, Vienna, Austria). Twenty-one different Harmonized Tariff Schedule (HTS) codes were queried to determine quantities (US tons, T) and breakdown of different soy product types being imported into the US from 2015 to 2020. A total of 78 different countries exported soy products to the US in 2019 and 2020, with top contributors being Canada (602,377 T and 530,759 T, respectively), India (438,563 T and 474,678 T, respectively), and Argentina (134,610 T and 87,602 T, respectively). In 2020, soy oilcake (641,846 T) was imported in the largest quantities, followed by organic soybeans (297,838 T) and soy oil (148,190 T). Of the 78 countries, 46 had cases of FAD reported through the World Organization for Animal Health (OIE) World Animal Health Information Database (WAHIS). Top exporters of soy products to the US from FAD+ countries in 2019 and 2020 were India (438,563 T and 474,678 T, respectively), Argentina (134,610 T in 2019), and Ukraine (44,415 T and 62,162 T, respectively). A system to monitor the sourcing of these products into the US and the end usage would allow for a greater understanding of the risk of these products to domestic swine herds.
Keywords: Soy imports; transboundary shipping; foreign animal disease; organic soybeans; soybean meal